Implementation of Beam Matching Concept for the New Installed Elekta Precise Treatment System Medical LINACs in Indonesia - O. A. Firmansyah; A. F. Firmansyah; S. I. Sunaryati; M. M. Putri; A. R. Setiadi; O. A. Akbar; V. Arif; C. Amelia (PPIKSN-BATAN, 2021)
A concept of radiation beam matching of some medical linear accelerators (LINACs) that have identical characteristics of the models, radiation quality, and multileaf collimator features may be implemented as long as the manufacturer provides complete specifications so that a Treatment Planning System (TPS) can be used for many beam-matched LINACs. This paper describes a preliminary study on the implementation of the beam matching concept for five units Elekta Precise Treatment System LINACs that have recently been installed in Indonesia. The beam matching criteria were based on the percentage depth dose (PDD) and beam profile for photon and electron beams. Dosimetry measurements were carried out by using an SNC 125 ionization chamber of 0.125 cm3 in volume, PTW Pinpoint 3D of 0.016 cm3 in volume, and PTW Farmer Chamber of 0.6 cm3 in volume. The results indicated that the PDD10 of 6 and 10 MV photon beams among installed five units LINACs have excellent compatibility each others with a maximum deviation of less than 0.4 %, while the maximum deviation for dose depth of 80 % (R80) for the electron beams with nominal energies of 4, 6, 8, 10, 15 and 18 MeV is 1 mm. The measurement results for the flatness profile were less than 6 %, and symmetry profiles were less than 3 %. It also outlines the determination of the absorbed dose to water under reference conditions. The results of the calibration of output doses show that the absorbed dose in the water was 1 cGy ≈ 1 MU. The data obtained from measurements for each LINAC conform with the requirements of the beam matching process set by the manufacturer.